2022
DOI: 10.1186/s40359-022-00905-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of sleep disturbance and rumination on work-related burnout of nurses treating patients with coronavirus disease

Abstract: Background COVID-19 has created significant and unprecedented psychological distress on nurses working with COVID-19 patients. Nurses dealing with such psychological distress are prone to burnout. This study examined the mediating role of sleep disturbance and rumination in the association between psychological distress and work-related burnout of nurses treating COVID-19 patients. Methods A cross-sectional study was conducted from 26th February to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…Overall, the mean scores for psychological distress in present study was (23. 14 ± 8.09), which was close to the positive points (25 points) of psychological distress, [28] the psychological distress level was similar to in United Arab Emirates during the COVID-19 pandemic (27.13.7), [30] in Iran during the COVID-19 pandemic (29.5 ± 6.03), [31] in Chinese psychiatric nurses (24.3 ± 8.15), [32] Higher than Chinese nursing students (20.67 ± 6.14). [33] In addition, our findings showed that participants who with university or above education (25.0 ± 8.42, P < .01) or income perception was poverty (26.88 ± 9.07, P < .01) got higher psychological distress scores (see Table 1), indicating that they experienced severe psychological distress.…”
Section: Discussionsupporting
confidence: 68%
“…Overall, the mean scores for psychological distress in present study was (23. 14 ± 8.09), which was close to the positive points (25 points) of psychological distress, [28] the psychological distress level was similar to in United Arab Emirates during the COVID-19 pandemic (27.13.7), [30] in Iran during the COVID-19 pandemic (29.5 ± 6.03), [31] in Chinese psychiatric nurses (24.3 ± 8.15), [32] Higher than Chinese nursing students (20.67 ± 6.14). [33] In addition, our findings showed that participants who with university or above education (25.0 ± 8.42, P < .01) or income perception was poverty (26.88 ± 9.07, P < .01) got higher psychological distress scores (see Table 1), indicating that they experienced severe psychological distress.…”
Section: Discussionsupporting
confidence: 68%
“…For example, Song et al found poor sleep quality exhibited strong positive associations with job burnout among Chinese nurses through SEM analysis ( 29 ). In addition, research based on nurses who treated patients diagnosed with COVID-19 revealed sleep disturbances posed a significant mediating effect on the relationship between psychological distress and burnout, which indicated sleep problems may affect burnout of nurses ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses dealing with psychological distress are prone to burnout (Zarei & Fooladvand, 2022). Negative thoughts related to psychological distress consume certain cognitive resources, resulting in insufficient cognitive resources to deal with more important tasks, which will reduce one's work enthusiasm and lead to burnout in the long run.…”
Section: Discussionmentioning
confidence: 99%